2018
DOI: 10.1097/md.0000000000012079
|View full text |Cite
|
Sign up to set email alerts
|

Ankle joint dislocation treating dislocated trimalleolar fractures accompanied with the complex posterior malleolus fracture without separation of the tibiofibular syndesmosis

Abstract: To explore the therapy of ankle joint dislocation treating dislocated trimalleolar fractures accompanied with the complex posterior malleolus fracture without separation of the tibiofibular syndesmosis and improve surgical results.Patients who had dislocated trimalleolar fractures accompanied with the complex posterior malleolus fracture without separation of the tibiofibular syndesmosis were retrospectively analyzed and 30 patients were enrolled the study. They were all treated by ankle joint dislocation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…There is even an excellent classification in three types [20] . In our case, the posterior malleolus fracture was not accompanied by a lower syndesmal diastasis, a fact reported by some authors [21] . Reduction of the fracture of the talus neck from posterior to anterior is a feasible alternative and sufficient anatomical restoration is achieved [22] .…”
Section: Discussionsupporting
confidence: 80%
“…There is even an excellent classification in three types [20] . In our case, the posterior malleolus fracture was not accompanied by a lower syndesmal diastasis, a fact reported by some authors [21] . Reduction of the fracture of the talus neck from posterior to anterior is a feasible alternative and sufficient anatomical restoration is achieved [22] .…”
Section: Discussionsupporting
confidence: 80%
“…[3][4][5][6][7][8][9][10] As far as the outcomes of the treatment of unstable ankle fractures are concerned, most studies reported excellent or good results with these scores. 14,16,[18][19][20][21][24][25][26][29][30][31][32][33][34]39,43 Surgical fixation is mostly preferred over conservative treatment as it consistently returns better outcomes. 7,13,17,26,32,38,42 Particularly, surgery allows for shorter immobilization and earlier weight-bearing leading to better functional scores and higher rates of return to normal life.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent and good results were 93.3%. 18 In 1985 Phillips proposed a 115-points system to document subjective and functional outcomes, including arthritis grading. 9 In this system, overall scores from 110 to 115 were classified as excellent, 96 to 109 as good, 70 to 95 as fair, and less than 70 as poor.…”
Section: Data Collectionmentioning
confidence: 99%
“…The common causes for such injure mainly include dysplasia of medial malleolus, insufficient talus coverage, ligament relaxation, and fibula muscle weakness. [ 2 ] Previous studies have reported that the incidence of isolated ankle dislocation approximately is 0.065%, and it is more common in male patients. [ 3 ] Actually, sports injuries and traffic accidents are the main causes of such injuries, [ 4 ] and forced inversion or eversion caused by high-energy violence is the main injury mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, isolated ankle joint dislocation without concomitant fractures of medial or lateral malleolus is uncommon in the clinical practice. [ 2 ] In the present study, we report a case of open total dislocation of ankle joint without fractures in a patient who obtained a satisfactory clinical result following early debridement and irrigation, one-stage repairment of ligaments, and plaster external fixation.…”
Section: Introductionmentioning
confidence: 96%